Kurikulum Tahfiz Al-Qur’an: Studi Kasus di Madrasah Aliyah Swasta Purbalingga - Chully, Ardan By; Fajar, Abbas Sofwan Matlail (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The paradigm that must be shifted is none other than a dichotomous view of science. Intelligence in the success of learning is the core of the curriculum. Curriculum development will continue to develop to provide innovation in education, of course, to determine the seriousness of the talents and interests of students in learning. This paper focus on Tahfiz Al-Qur'an Curriculum at Private Madrasah Aliyah in Purbalingga, with the following research questions (1) how to plan the tahfiz Al-Qur'an curriculum (2) how to implement the curriculum tahfiz Al-Qur'an (3) how to evaluate the tahfiz Al-Qur'an curriculum. This research is qualitative research with a case study design. Data collection techniques through participant observation, in-depth interviews, and documentation. Meanwhile, for data analysis, researchers used flow model analysis which included; data condensation, data display, and conclusion drawing. The research results are: (1) planning the tahfiz Al-Qur'an curriculum using the standard curriculum process consisting of; Curriculum Planning, Syllabus, and lesson plans. (2) implementing the tahfiz Al-Qur'an curriculum uses three memorization methods: Talaqi Method, Takrir Method, and Tasmi' Method. (3) evaluation of curriculum development using formative assessment in form (daily assessment in the deposit book) and summative form (rewards to students, semester exams, student report cards).